On the Derived Length of a Finite Group with Complemented Subgroups of Order $p^2$ - Knyagina, V. N.; Monakhov, V. S.; Княгина, В. Н.; Монахов, В. С.; Княгина, В. Н.; Монахов, В. С. (Institute of Mathematics, NAS of Ukraine, 2015)
It is shown that a finite group with complemented subgroups of order $p^2$ is soluble for all $p$ and its derived length does not exceed 4.